Examining the role of menthol cigarettes in progression to established smoking among youth. (November 2019) - Nonnemaker, James; Feirman, Shari P.; MacMonegle, Anna; Ambrose, Bridget K.; Jackson, Kia J.; Schroeder, Megan J.; Smith, Alexandria A.; Ridgeway, William; Rass, Olga
Abstract: Background: Menthol, a flavoring compound added to cigarettes, makes cigarettes more appealing to youth and inexperienced smokers and increases cigarettes' abuse liability. However, limited studies are available on menthol's role in smoking progression. Methods: To assess the association between menthol in cigarettes and progression to established smoking, we used five waves of data from the Evaluation of Public Education Campaign on Teen Tobacco Cohort Study, a nationally representative longitudinal survey of U.S. youth conducted as part of "The Real Cost" evaluation. We used discrete time survival analysis to model the occurrence of two event outcomes—progression to established, current smoking and progression to established, frequent smoking—using a logit model with a menthol use indicator as the key explanatory variable. Based on this framework, we estimated the effect of prior menthol use on the odds of smoking progression. Results: In the progression to established, current smoking model, prior menthol use was significantly associated with progression [adjusted odds ratio (aOR) = 1.80, p < .05, confidence interval (CI) = (1.03–3.16)]. While results were in a similar direction for the model of progression to established, frequent smoking, the association between prior menthol use and this progression model did not reach significance [aOR = 1.56, CI = (0.80–3.03)]. Conclusion: The results suggest a relationship between using menthol cigarettes and progression from experimental to established, current smoking among youth. This study adds to a growing literature base that supports that menthol cigarettes, compared to nonmenthol cigarettes, put youth at increased risk for regular cigarette use. Highlights: Used survival analysis to model the effect of menthol on youth smoking progression Menthol use was associated with progression to established current smoking. Results suggest menthol puts youth at increased risk for future regular cigarette use.